Study the Role of Selenium or Zinc as Organic form on some Antioxidant and Liver Enzymes of Rams (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was conducted to detect the role of the organic form of Selenium or Zinc that supported withyeast (Saccharomyces cerevisiae) on the liver function and antioxidant enzymes. Twenty-one rams that theiraverage weight of 38±2 kg. The males divided into three groups. The first group (G1) late without treatment,group two (G2) was administrated with (Saccharomyces cerevisiae-Zinc) (0.2 g/kg/ body weight), whilegroup three (G3) was administrated with (Saccharomyces cerevisiae-Selenium) (0.03 g/kg/ body weight).Blood samples were collected from males at zero 45 and 90 days of experiment. The results of AST, ALT andALP showed non-significant differences between different groups. While the activity antioxidant enzymesrecorded a significant improvement, through a significant increased (P?0.05) of Glutathione peroxidase andcatalase concentrations of the group that treated with organic selenium or zinc compare with a control group,from another hand, the treated group with organic selenium has been shown the significant increases (P?0.05)of Glutathione peroxidase compared with the animals that treated zinc at the third period. Whereas, the treatedgroups recoded a significant increment (P?0.05) with the progress of ages. From results concluded that thefeeding selenium and zinc as an organic form that fortified by yeast Saccharomyces cerevisiae significantlyincreases antioxidant enzyme activity and have a protective role to the liver.